Toy Story How Pixar Reinvented the Animated Feature - Smith, Susan; Brown, Noel; Summers, Sam (Animation: Key Films/Filmmakers, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Toy Story (John Lasseter, 1995), Pixar's first feature-length production and Hollywood's first completely computer-generated animated film, is an international cultural phenomenon. This collection brings together a diverse range of scholars and practitioners who together explore the themes, compositional techniques, cultural significance and industry legacy of this landmark in contemporary cinema. Topics range from industrial concerns, such as the film's groundbreaking use of computer generated imagery and the establishment of Pixar as a major player in the animation world, to examinations of its music, aesthetics, and the role of toys in both the film and its fandom. TheToy Story franchise as a whole is also considered, with chapters looking at its cross-generational appeal and the experience of growing up alongside the series. As the first substantial work on this landmark film, this book will serve as an authoritative introduction for scholars, students and fans alike.